EFEKTIVITAS PENGGUNAAN MEDIA DRUM UNTUK MENINGKATKAN PENGENALAN BILANGAN 1 – 10 BAGI ANAK TUNARUNGU DI SLB SABILUNA PARIAMAN - Silvi - Harmaini (Universitas Negeri Padang, 2012)
this study begins with the observation by the author in SLB Sabiluna Pariaman, found that deaf children do not been able to show aims to prove that through the medium of drumcan improve recognition number 1-10 for children with hearing impairment in SLB Sabiluna Pariaman. Subjects with hearing impairment is one person who sits in class D.1B. this type of study is a single subject research method to see the trend graphs that compare the baseline is not given treatment. The procedure of data recording by means of direct observations of media drum providedto children in raising familiar number of 1-10. Data recorded by event recording procedure is to give a check mark(V) at a number that is read correctly. Data analysis of graphs. The results are analyzed include the number of observations at five times thee baseline condition, treatment condition as much as six times and five times the baseline. The result indicate that the drum through the media can increase significantly the introduction of number 1-10. This is evident from the results of the analysis is the tendency to increase. At baseline condition the ability to correctly recognize number 1-3. After being treated by the media drum proven ability to recognize the increasing numbers of children can recognize number 1-10 correctly. So the researcher suggest to the teacher to apply learning with media druma to boost the introduction of number 1-10 for number 1-10 for further learning.